International Joint Conference: 12th International Conference on Computational Intelligence in Security for Information Systems (CISIS 2019) and 10th International Conference on EUropean Transnational Education (ICEUTE 2019) Seville, Spain, May 13th-15th, 2019 Proceedings - Martínez Álvarez, Francisco; Troncoso Lora, Alicia; Sáez Muñoz, José António; Quintián, Héctor; Corchado, Emilio (Advances in Intelligent Systems and Computing, 2020)
XVIII, 350 p. 121 illus., 85 illus. in color.